"Diels-Alder reaction" in the ionic version: GaCl3-promoted formation of substituted cyclohexenes from donor–acceptor cyclopropanes and dienes. Issue 25 (18th June 2020) - Belaya, Maria A.; Knyazev, Daniil A.; Novikov, Roman A.; Tomilov, Yury V.
Graphical abstract: Highlights: A new reaction of donor–acceptor cyclopropanes with dienes is suggested. This process is promoted by GaCl3 and occurs via 1, 2-zwitterions. It involves formal [2 + 4]-cycloaddition to the diene system. The process is similar to the Diels-Alder reaction in ionic version. Resulting structures have a functional substituted cyclohexene skeleton. Abstract: A selective process of formal [2 + 4]-cycloaddition of donor–acceptor cyclopropanes (2-arylcyclopropane-1, 1-dicarboxylates) in the presence of GaCl3 to conjugated dienes to give cyclohex-3-ene-1, 1-dicarboxylates has been developed. This process occurs by generation of 1, 2-zwitterionic gallium complexes and involves the addition of a carbocationic center to a terminal diene atom followed by 1, 6-cyclization to the allyl position of the resulting intermediate.